(untitled) (Journal of the College of Basic Education, 2024)
The aim of the current research is to investigate the impact of pre-summary strategies on achievement and retention among second-grade middle school female students in the subject of chemistry. To achieve this goal, the researcher employed an experimental method, specifically using two groups: the experimental group and the control group. The purpose is to achieve the desired education and reach the required educational and pedagogical objectives, as well as to address all challenges faced in the educational process. Consequently, there arose a need to employ various teaching methods, especially for scientific subjects like chemistry. Among these methods, the researcher chose the pre-summary strategy, which is one of the effective pre-teaching strategies. It is equally important as the teaching strategies used to facilitate the learning process and clarify it. Pre-summaries provide students with a comprehensive and general perspective, preparing them for the material presented. Additionally, they play a crucial role in summarizing the study material, conveying key points accurately and concisely to students. Through the adoption of this pre-teaching strategy, the researcher aimed to assess its impact on the achievement and retention of second-grade middle school female students in the subject of chemistry. The research hypotheses are as follows: There are no statistically significant differences at the 0.05 level between the average scores of female students who studied using the pre-summary strategy and those who studied using the conventional method in the achievement test. There are no statistically significant differences at the 0.05 level between the average scores of female students who studied using the pre-summary strategy and those who studied using the conventional method in the retention test. Based on the research results, the following conclusions were drawn: There are statistically significant differences at the 0.05 level between the average scores of female students who studied using the pre-summary strategy and those who studied using the conventional method in the post-test achievement among second-grade middle school students in the subject of chemistry. There are statistically significant differences at the 0.05 level in favor of the experimental group, which studied using the pre-summary strategy, compared to the control group, which studied using the conventional method, in the retention test among second-grade middle school students in the subject of chemistry